Assessing aquifer vulnerability near cemeteries using dipole-dipole and vertical electrical sounding methods - Idowu Ilaboya; Eghosa Omosefe; Esther Ambrose-Agabi (CTU Journal of Innovation and Sustainable Development)
An integrated geophysical investigation of the second cemetery in Benin City was conducted with the view to determine the leachate flow direction and the geoelectrical layers that characterized the underlying aquifer. Eight vertical electrical soundings (VES) and two dipole-dipole profiling lines along two transverse sections were carried out. For the dipole-dipole profiling, ABEM Terrameter SAS 300C was employed, while the VES investigation utilized the Schlumberger array. The resistivity data collected during the field investigation were interpreted using DIPROWIN software version 4.01. Leachate plume was identified in the subsurface soil at a depth range of 5 to 20 meters. This was attributed to the soil porosity, aiding the infiltration of necroleachate. The VES results revealed four geoelectric layers: topsoil, lateritic soil, a weathered layer (composed of clay), and medium to coarse sand. The overburden exhibited a thickness range of 0.7762m to 0.8074m, resistivity ranging from 57.318Ωm to 2831.4Ωm, and depths ranging from 0.7762m to 1.5836m. The third geoelectric layer, identified as clay, had an average thickness of 11.48 meters at a depth of 13.06 meters, with a resistivity of 203.52Ωm. Apart from acting as a seal against the downward penetration of leachate, the clay also serves as a filter.